COMPLEX EVALUATION PARAMETERS OF CENTRAL AORTIC BLOOD PRESSURE AND MAIN ARTERIES STIFFNESS IN PATIENTS WITH CORONARY ARTERY DISEASE, DEPENDING ON THE PREVALENCE OF ATHEROSCLEROSIS - U. I. Nizamov; F. M. Bekmetova; Sh. U. Khoshimov; A. B. Shek; R. D. Kurbanov (Евразийский Кардиологический Журнал, 2015)
Objective: to study the parameters of central aortic blood pressure and main arteries stiffness in patients with coronary artery disease (CAD) depending on the prevalence of atherosclerotic lesions. Material and methods: the study involved 90 patients with a diagnosis of unstable angina class II B (E. Braunwald et al., 1989) the control group consisted of 27 healthy people. The method of applanation tonometry using the apparatus of SphygmoCor («AtCor Medical», Australia) studied the performance stiffness: pulse wave velocity (PWV) and augmentation index (AIx). Coronary angiography was performed at the facility Allura CV-20 (Philips, The Netherlands), the state of the carotid arteries was studied by duplex ultrasonography, evaluation of involvement of femoral arteries was based on ankle-brachial index